Social sources of work motivation related to healthcare workers’ emotional engagement, absenteeism and turnover during the COVID-19 pandemic - Roussillon Soyer, Claude; Gagné, Marylène; Balkin, David (Management international / International Management / Gestiòn Internacional, 2023)
This study examined the effect of socially controlled motivation for caregivers on turnover intentions and absenteeism within the COVID-19 context. We applie a self-determination theory framework to analyze the effect of external social regulation as mediated by emotional engagement on turnover intentions and absenteeism. The data for this study came from survey and archived data of 303 caregivers in ten nursing homes in France. Our findings show that the external social regulation dimension was related positively to emotional engagement which in turn mediated a negative relationship to the turnover intentions and absenteeism of caregivers. We discuss how expressions of social approval can promote caregivers’ retention.